Restoration of endodontically treated mandibular third molar tooth with indirect bonded restoration using morphology-driven preparation technique: A case report - Hurint, Theresia PL.; Dwiandhany, Wahyuni S.; Nugroho, Juni J.; Hikmah, Noor; Natsir, Nurhayaty; Trilaksana, Aries C. (Hasanuddin University, 2023)
Objective: The aim of this case report is to describe treatment management restoration after endodontic reintervention treatment with indirect bonded restoration using morphology- driven preparation technique.Methods: The preparation technique that can be used is morphology driven, preparation design, while consider bio emulation criteria such as the height of contour, sigmoid nature of enamel dentin interface, and the direction of enamel rods with respect to axial and proximal surfaces. This preparation technique improves resistance by preserving dentin and enamel, also increases bond strength by improving the quality of bonding substrate, marginal integrity and aesthetics.Results: The tooth was inadequately treated about two months ago which made the clinician decided to do an endodontic reintervention. After that, an indirect restoration with lithium disilicate was planned for the patient. The preparation design is a long-wrap overlay, butt-join preparation in the interproximal box (1 mm – 1.2 mm) and rounded inside angles.Conclusion: Restoration after reintervention endodontic treatment with indirect bonded restoration using morphology-driven preparation techniques shows successful treatment with periapical tissue healing and good tissue response.